Emigrants, Refugees, and the Post-Colonial Novel, or the In-Between as an Articulatory Space. Editorial Introduction - Natalia Lemann; Donna Landry (Zagadnienia Rodzajów Literackich)
The issue of emigration and refugees is one of the major global problems of the contemporary world. The challenges faced by nations, states, and cultures in the face of the above-mentioned phenomena include issues of social, historical, and cultural policy, but also an ethical dimension and the character of practical social involvement. Challenges to work through historical legacies and traumas in a spirit of respect for difference and the cultural legacy of peoples who were once colonised play an extremely important role. The multicultural tendency of the politics of history is inclined towards a project of entangled history or histoire croisée. In the context of increased emigration phenomena, it is necessary to rework and refashion the notion of nation, to remove from it the traces of an essentialist approach marked by nationalism and ethnocentrism. The most important challenge, however, is to change the way we think about the concepts of nation, emigration, and exile, i.e., to ‘decolonise minds’. The postcolonial novel is a literary genre that is closely related to the aforementioned challenges. The key issues of the postcolonial novel are emigration and exile. The genre addresses the theme of emigration both synchronically, diagnosing current problems, but also historically, recalling the colonial conditions of current relations. Emigrant narratives are about articulating the experience of being between cultures, countries, and times. The postcolonial novel provides an insight into the dynamics of changing attitudes of successive generations of emigrants towards the culture of the ancestral country and the country of present residence. The generational dynamics of the postcolonial and expatriate novel show the transformation of rhetoric from nostalgia to irony. As proposed by Rosi Braidotti, one can speak of a transition from the figure of the outlaw to that of the nomad; the figure subversively oriented, questioning all restrictions and top-down imposed political and cultural orders.